A review of extraction methods for the analysis of pharmaceuticals in environmental waters. Issue 21 (1st November 2020) - Daniels, Kevin D.; Park, Minkyu; Huang, Zhenzhen; Jia, Ai; Flores, Guillermo S.; Lee, Hian Kee; Snyder, Shane A.
Abstract: Pharmaceuticals play a vital role in the prosperity of human and veterinarian health by diagnosing, treating, or preventing diseases. Produced in large quantities for various applications, pharmaceuticals primarily enter the environment through wastewater systems. Historically, the ability to detect pharmaceuticals in environmental waters has been limited. However, growing technological advancements are changing pharmaceutical detection capabilities and our understanding of their occurrence in environmental waters. The analysis of pharmaceuticals in the environment began with simple gas chromatography-mass spectrometry and evolved to using liquid chromatography-tandem mass spectrometry as the dominant method. Many of these methods require sample extraction, with solid phase extraction (SPE) being the most popular. Additionally, miniaturized and on-line extraction procedures have also attracted a lot of attention. Nevertheless, approaches involving large volume injections without the need for sample enrichment have made significant strides in recent years. The aim of this review is to provide an overview of extraction methods for environmental water samples containing trace levels of pharmaceuticals and how current applications will mold how they are analyzed in the future. Graphical Abstract: UF0001